A relevância dos processos no índice de desempenho da saúde suplementar: estudo de caso em uma operadora de planos de saúde de Fortaleza - Oliveira, Jonny César Cavalcante de (2011)
This paper aims to identify the importance of procedures on private health plans for the outcome of the Performance Index of Supplementary Health (IDSS). It was identified and mapped the processes that impact the index IDSS, having the participation of the managers of each process, who determined how each process affects the result of the IDSS and made suggestions to improve the processes studied. This research is exploratory and descriptive according to its finality. As for the means, it is a case study based on field, bibliographic and documentary research. From the universe of study, composed by the companies’ providers of health plans based in Fortaleza, it was chosen a self-management operator having a portfolio around 40,000 beneficiaries. The subjects of research were employees of the operator with a management position, who underwent focused interviews and answered a questionnaire, where both had a qualitative treatment of the data collected. According to the managers surveyed, it was identified nine processes considered important for the calculation of the IDSS. Evaluating the research, it can be concluded that to obtain a good grade in the IDSS it is essential to have a good development of the team responsible to perform the activities. The study of the processes allowed to evaluate rationally how the activities should be done, who should run them and with the help of which tools.